Data exchanges among firms - Morad Elsaify; Sharique Hasan (Digital Business, 2021)
Firms are collecting more data-about their operations, customers, and markets-in order to improve performance. Some of this data has value beyond a firm's boundary and thus can create value for other firms. Yet, we have relatively few facts about the growing data exchange between firms, its participants, and the types and value of data bought and sold by firms. We present preliminary descriptive evidence about the emerging data market using the information on over 1600 data exchanges reported in the news between 2017 and 2018 executed by 1285 of the largest public and private firms. Our findings suggest that nearly 17% of these firms in our sample participate in the data market. Furthermore, 80% of the exchanges are for customer data, and over 50% of transactions are structured as mutual data sharing agreements rather than unidirectional sales. Among the firms in our sample, it is the largest firms in terms of valuation and those with significant data capabilities that buy and sell data. Moreover, we find that most exchanges appear to happen among firms in the same industry and with significant data science capabilities. These results suggest that the data exchanges and the market for data may be consequential and call for further research.
Keywords: 650; Firms; Data; Market for data; Strategy